2019
DOI: 10.1371/journal.ppat.1008048
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium kinesin-8X associates with mitotic spindles and is essential for oocyst development during parasite proliferation and transmission

Abstract: Kinesin-8 proteins are microtubule motors that are often involved in regulation of mitotic spindle length and chromosome alignment. They move towards the plus ends of spindle microtubules and regulate the dynamics of these ends due, at least in some species, to their microtubule depolymerization activity. Plasmodium spp. exhibit an atypical endomitotic cell division in which chromosome condensation and spindle dynamics in the different proliferative stages are not well understood. Genome-wide shared orthology … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
71
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(88 citation statements)
references
References 75 publications
(105 reference statements)
14
71
1
Order By: Relevance
“…5B). This mirrors what has been seen in electron microscopy studies: nuclear spindles radiate from the nuclear poles, with attached kinetochores within an intact nuclear membrane during oocyst development [30,32].…”
Section: Pbkinesin-5-gfp Exhibits Multiple Nuclear Foci During Oocystsupporting
confidence: 81%
See 2 more Smart Citations
“…5B). This mirrors what has been seen in electron microscopy studies: nuclear spindles radiate from the nuclear poles, with attached kinetochores within an intact nuclear membrane during oocyst development [30,32].…”
Section: Pbkinesin-5-gfp Exhibits Multiple Nuclear Foci During Oocystsupporting
confidence: 81%
“…The loss of kinesin-5 may have been compensated for by the over-expression of another member of the kinesin family, therefore we analysed the transcript level of kinesin-8B, kinesin-8X and kinesin-13 in gametocytes of Δ kinesin-5 parasites. These kinesins are highly expressed in gametocytes and have important role during male gametogony [23,30]. We found that the kinesin-13 transcript level was significantly upregulated ( Fig.…”
Section: Pbkinesin-5 Is Dispensable For Cell Division During the Diffmentioning
confidence: 68%
See 1 more Smart Citation
“…The loss of kinesin-5 may have been compensated for by the over-expression of another member of the kinesin family, therefore we analyzed the transcript level of kinesin-8B, kinesin-8X and kinesin-13 in gametocytes of Δkinesin-5 parasites. These kinesins are highly expressed in gametocytes and have important role during male gametogony ( Zeeshan et al., 2019a ; Zeeshan et al., 2019b ). We found that the kinesin-13 transcript level was significantly upregulated ( Figure 1M ), suggesting that higher levels of kinesin-13 may - in some way - compensate for the kinesin-5 deletion.…”
Section: Resultsmentioning
confidence: 99%
“…As cell division in Plasmodium is atypical, so the molecules regulating cell division are also divergent from those of higher eukaryotes ( Tewari et al., 2010 ; Guttery et al., 2014 ; Roques et al., 2015 ; Wall et al., 2018 ). The large family of kinesins includes molecular motors that are essential for several processes during cell division ( Wordeman, 2010 ; Yount et al., 2015 ), and in Plasmodium berghei there are nine kinesin genes, including two kinesin-8 genes that are important in cell division and male gamete formation ( Zeeshan et al., 2019a ; Zeeshan et al., 2019b ). There is a single Plasmodium kinesin-5, and since this protein plays an important role during cell proliferation in many eukaryotes, and is considered as a strong target for the development of therapeutics against many diseases including malaria ( Liu et al., 2014 ), we decided to study its role during cell division in the malaria parasite.…”
Section: Introductionmentioning
confidence: 99%